Analisis Minat Menabung di Bank Syariah Pada Santri Pondok Pesantren Attaqwa Pusat Putri Bekasi - Kholidatul Fikriyah; Rafika Rahmawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the saving interest of the students of the Attaqwa Islamic Boarding School at the center of the Putri Bekasi. The data used are primary data and secondary data, carried out using questionnaires, books and journals and the type of sampling using purposive sampling method. The sample in this study was the students of the Attaqwa Islamic Boarding School at the center of the Putri Bekasi, which amounted to 177 respondents. The results showed that the results of the F test with a simultaneous test had a significant positive effect, namely the interest in saving at the Attaqwa Islamic boarding school at the center of the Putri Bekasi was jointly influenced by promotion, religiosity and knowledge. And the results of the partial test of the variables of promotion, religiosity and knowledge have a significant positive effect on the saving interest of the students of the Attaqwa Islamic Boarding School in the center of the Putri Bekasi.